Design of field programmable gate array-based data processing system for multi global positioning system receiver - Zainul Abidin; Nauval Aryawiratama; Adharul Muttaqin; Ryoichi Miyauchi (Institute of Advanced Engineering and Science, 2022)
A global positioning system (GPS) sensor is needed for a ballistic/moving object to do position tracking. In previous study, a multi GPS processing system was made using several microcontrollers and data processing cannot be done simultaneously. Therefore, it was considered as ineffective system. In this research, field programmable gate array (FPGA)-based data processing system for multi-GPS receiver was proposed. The proposed system was designed to reduce root mean square error (RMSE). There are two main processes in the proposed system which work in parallel, i.e. data parsing and data processing. Raw data from GPS receiver was collected and calculated to get average value, then sent it through serial communication to show result. Experimental results confirm the RMSE value of the proposed system is smaller than the conventional one. The RMSE for latitude, longitude, and altitude decrease by 38.46%, 58.28%, and 24.80%, respectively.